Information documents of the GPU–OGPU in 1920s: experience of text mining (based on materials from the North Caucasus) - Alexander Yu. Rozhkov; Timofey A. Runaev (Кавказология)
Using mass sources in historical research makes it possible to improve the representativeness of knowledge about the historical period. However, qualitative text analysis has limitations when working with a large array of data. Thus, in modern historical science is a need to involve computer («intellectual») analysis of texts for processing mass sources. Based on principles of the discourse-historical approach, authors indicated the possibility of using the RStudio computer program for intellectual analysis of the voluminous corpus of information reports and reviews of the GPU–OGPU of the 1920s on the materials of the North Caucasus. In the first stage, the contextualization of the studied sources was carried out. The authors found that reports and reviews of the GPU-OGPU of different years had similar terminological, emotive and thematic composition. While maintaining the internal unity of the OGPU information documents on the North Caucasus, an increase in the number of topics in summaries and reviews has been revealed since 1925. Emotional aggravation and complication of the «Chekist» discourse intensified so much by the end of the 1920s that terminological composition of the documents of 1928-1929 differed significantly from composition of texts of previous years. Thus, the text mining of the reports and reviews of the GPU–OGPU demonstrated the transformation of the regional «Chekist» discourse, which was broadcast to the top leadership of the country. The applied approach allows minimizing subjectivity of researcher’s assessments and conclusions.